The roles of interpersonal skills for teachers to learn Islamic Religious Education online - Cahyono, Guntur; Purnomo, Purnomo (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
The purpose of this research is to find out about the problems of applying interpersonal skills for Islamic Religious Education teachers in remote Islamic Religious Education learning at Kartasura District Middle School in 2021 and its alternative solutions. This study used a field qualitative method. Interviews and observation results provide primary data. Secondary data in the form of documentation is studied to obtain a clear picture of the research subject. This study shows that the problems of interpersonal communication between teachers and students during distance Islamic education learning are in the form of 1. Online media makes communication less memorable, tiring, and unidirectional. 2. To improve effective communication, teachers must spend more time outside of the classroom and involve students' parents. 3. There are distractions in the student and teacher environment that interfere with attention. Alternative solutions to these problems are: 1. Teachers need to emphasize the importance of quality communication over quantity and duration through role distribution for all students and refreshing students' minds before learning. 2. Fellow Islamic Education teachers and teachers in other fields of study can create collaborative learning to maximize the teaching process and also enable assignments that can accommodate cross-subject material. 3. Teachers need to strengthen effective relationships and communication to reduce the effects of environmental distractions.Tujuan penelitian ini adalah untuk mengetahui bagaimana problematika penerapan keterampilan interpersonal bagi guru PAI dalam pembelajaran PAI jarak jauh di SMP Kecamatan Kartasura tahun 2021, dan alternatif solusinya. Penelitian ini menggunakan metode kualtiataif lapangan. Data primer berasal dari wawancara dan hasil obeservasi. Data skunder berupa dokumentasi dikaji untuk mepadapatkan gambaran yang lugas tentang subyek penelitian. Penelitian ini menunjukkan bahwa problematika komunikasi interpersonal antara guru dan siswa selama pembelajaran PAI jarak jauh, berupa: 1. Media daring menjadikan komunikasi kurang berkesan, melelahkan dan terkesan searah. 2. Guru memerlukan waktu tambahan di luar kelas dan melibatkan orang tua siswa untuk meningkatkan komunikasi efektif. 3. Ada distraksi di lingkungan siswa dan guru yang mengganggu atensi. Alternatif solusi untuk problematika tersebut adalah: 1. Guru perlu menekankan pentingnya kualitas komunikasi bukan pada kuantitas dan durasi melalui distribusi peran bagi seluruh siswa dan penyegaran pikiran siswa sebelum pembelajaran. 2. Sesama guru PAI maupun guru bidang studi lain dapat menciptakan pembelajaran kolaboratif untuk memaksimalkan proses pengajaran dan memungkinkan juga penugasan yang dapat mewadahi materi lintas mata pelajaran 3. Guru perlu menguatkan relasi dan komunikasi efektif untuk mengurangi efek distraksi lingkungan.Â